2008
DOI: 10.1021/mp7001494
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutically Active Natural Product Synthesis and Supply via Plant Cell Culture Technology

Abstract: The chemical diversity of plant-derived natural products allows them to function in a multitude of ways including flavor enhancers, agricultural chemicals, and importantly, human medicinals. Supply of pharmaceutically active natural products is often a challenge due to the slow growing nature of some species, low yields found in nature, and unpredictable variability in accumulation. Several production options are available including natural harvestation, total chemical synthesis, semisynthesis from isolated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
139
0
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(150 citation statements)
references
References 113 publications
0
139
0
11
Order By: Relevance
“…Paclitaxel is found in only small quantities in plants, and total synthesis comprises several steps, and is therefore lowyielding. The main current sources of paclitaxel are semi-synthesis from abundant advanced precursors derived from the needles of yew plants and from Taxus suspension cell cultures (2)(3)(4). The biosynthetic pathway leading to paclitaxel has been partially elucidated (5) (Figure 1), but improved understanding of the four or five undefined pathway steps and the overall regulation of paclitaxel synthesis are needed in order to enable bioengineering approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Paclitaxel is found in only small quantities in plants, and total synthesis comprises several steps, and is therefore lowyielding. The main current sources of paclitaxel are semi-synthesis from abundant advanced precursors derived from the needles of yew plants and from Taxus suspension cell cultures (2)(3)(4). The biosynthetic pathway leading to paclitaxel has been partially elucidated (5) (Figure 1), but improved understanding of the four or five undefined pathway steps and the overall regulation of paclitaxel synthesis are needed in order to enable bioengineering approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative studies between in vivo and in vitro material (calli) to quantify secondary metabolites have been conducted for species like Vaccinium macrosporum and Buddleja cordata (Madhavi et al, 1995;Estrada-Zuniga et al, 2009). Presently, however, very few successful examples of the commercial application of cellular suspensions exist due to the low biosynthesis of the compound, differentiation and compartmentalization of cells, lack of developing organelles, unstable cellular lines and the difficulty of scaling production (Kolewe et al, 2008;Estrada-Zuniga et al, 2009).…”
Section: Quantification Of T-r and T-p In Plant Materialsmentioning
confidence: 99%
“…It is shown that more than 60 medicinal plants have higher content of metabolites in culture cells than in original species [11]. In particular, plant cell suspension cultures containing undifferentiated cells are attractive due to their relative similarity to microbial cell culture systems [12]. L. macranthoides Hand.-Mazz.…”
Section: Introductionmentioning
confidence: 99%